Sudden Cardiac Death in a Neonate Due to Bilateral Absence of Coronary Artery Ostium - Bailey, Nicole A; Aldawsari, Khalifah A; Zeidenweber, Carlo M; Khan, Danyal M (Journal of Cardiology and Cardiovascular Medicine, 2023)
Introduction: Congenital heart disease is a leading cause of neonatal mortality linked to birth defects. Despite the widespread availability of prenatal screenings, detection rates remain low. Accurate early detection of these lesions is pivotal to reducing neonatal morbidity and mortality. Methods: In this case, we present a neonate who experienced sudden cardiac death due to a rare, undiagnosed congenital cardiac anomaly - the bilateral absence of coronary artery ostium. Discussion: This case highlights the importance of prenatal detection of congenital cardiac anomalies. While fetal echocardiography is frequently utilized, it only identifies CHD in 36-50% of cases. This is attributed to inadequate imaging procedures, varied operator skills, and regional discrepancies. Early detection of severe CHD is essential for specialized treatment, thereby mitigating neonatal health risks and improving survival rates. Conclusion: Prenatal detection of CHD, especially coronary anomalies, continues to pose significant challenges. There is a pressing need to establish and enforce standardized protocols for fetal echocardiography aimed at these anomalies. To enhance care and improve outcomes, a joint effort between academic institutions and community centers is encouraged. Congenital coronary artery anomalies are a significant cause of sudden cardiac death in children. The absence of a coronary artery ostium is known to be associated with other congenital heart diseases, particularly pulmonary atresia with an intact ventricular septum. However, isolated coronary disease has also been reported in this case. Prenatal echocardiography is a valuable tool for diagnosing congenital heart disease. However, certain limitations may be encountered when diagnosing coronary artery anomalies.